Solar Panel Technologies for MRTS: A Pathway to Sustainable Urban Transportation (International Journal of Scientific Research in Science and Technology, 2025)
Solar energy is a key driver of sustainable energy transitions, offering an alternative to fossil fuels while aiding in the achievement of global climate targets. Nevertheless, traditional horizontal solar panel setups encounter limitations related to space and efficiency, primarily due to issues concerning tilt and angle of incidence. This review article explores the feasibility of vertically oriented solar panels, particularly in the context of Mass Rapid Transit Systems (MRTS) in India, where maximizing return on investment (ROI) is crucial. A comparative assessment of monocrystalline, polycrystalline, and thin-film solar panels is conducted to analyze their efficiency, cost-effectiveness, and suitability for MRTS applications. Case studies from Delhi Metro, London Underground, and Tokyo Metro reveal both challenges and opportunities associated with solar integration. The results indicate that thin-film panels, owing to their flexibility and adaptability, are the most appropriate choice for MRTS, while monocrystalline panels provide superior efficiency. The study concludes with suggestions for enhancing solar energy integration in MRTS through technological innovations and supportive policies.
Keywords: MRTS; Solar Energy; Solar Technologies; Solar panel; Sustainability